CONSUMPTION OF BLOOD SUPPLEMENT TABLETS (TTD) ON THE INCIDENT OF ANEMIA IN TEENAGERS AT MTs SITI KHADIJAH TAPIN DISTRICT - Fenny Yuniarti; Bardiati Ulfah; Rizki Amalia (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2024)
Adolescence is a transition period from child to adult that goes through several important developmental stages in life. To produce a healthy and intelligent generation, healthy young women are needed from an early age, both physically and mentally. The health problem in adolescents based on adolescent health program screening is the incidence of anemia. Based on data from 13 Community Health Centers in Tapin Regency, North Tapin Community Health Center was recorded as having the highest anemia rate in adolescents, reaching 51.28%, obtained from 9 middle and high schools and equivalent. The aim of the research is to determine the relationship between consumption of blood supplement tablets (TTD) and the incidence of anemia in young women at MTs Siti Khadijah, Tapin Regency. The study used a retrospective design method. The population was 70 people, taking the entire population as a sample. The research results based on the Mann Withney test obtained a significance value of 0.000<α (0.05), which means that H_0 was rejected, meaning there was a relationship between the level of blood supplement tablet consumption and the incidence of anemia in teenagers at MTs Siti Khadijah, Tapin Regency. There is a need to increase continuous efforts and provide assistance to teenagers from health workers, teachers and parents in providing health education to young women, especially the importance of consuming blood supplement tablets to prevent anemia